A Study On The Use Of Retelling Story Technique In Teaching Speaking Skill - Rivaldo Barani; Darmawan Darmawan; Wahyudin Wahyudin (Hasanuddin University, 2026)
Retelling story is widely used as a technique to support students’ speaking development in English language classrooms. This study aims to describe how the retelling story technique is implemented in speaking classes and to examine its effects on students’ speaking skills at different academic levels. This study employed a qualitative library research design by analyzing five previous research studies that investigated the use of retelling story in teaching speaking skills. The selected studies were conducted at different educational levels and were reviewed to identify instructional procedures, supporting media, and reported learning outcomes. The results of the analysis show that all five studies applied the retelling story technique through three main stages: pre-retelling activities, during-retelling activities, and post-retelling activities. These stages were consistently referred to as before, during, and after retelling activities. The implementation of the technique was often supported by additional media and methods, such as YouTube videos, picture series, and guided questions, to help students understand and retell stories more effectively. Furthermore, the findings indicate that students at different academic levels showed improvement in their speaking skills after the application of the retelling story technique. Students became more active in classroom interaction and demonstrated increased confidence in expressing ideas orally. The reviewed studies also reported that students were more motivated and independent when retelling stories. Overall, the findings suggest that the retelling story technique has a positive effect on students’ speaking skills and can be considered an effective strategy for teaching speaking in EFL classrooms.